Optimizing the Preparation of Fish-based Snack Chips Using Response Surface Methodology - Veena, M.; Sravani, K.; Dhanapal, K.; Madhavan, N.; Kumar, G. Praveen; Sai, J. Venkata; Praneeth, A.; Kumar, S. Jyothi Ram (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during the months of May to August in the year 2025 at the Department of Fish Processing Technology Laboratory, to study the optimization of fish-based snack chips through Response Surface Methodology (RSM) at College of Fishery Science, Muthukur. The increasing consumption of ready-to-eat snack foods has resulted in a higher intake of energy-dense products with limited nutritional value, particularly low protein content. Fish, being a rich source of high-quality protein and essential nutrients, offers significant potential for the development of nutritionally enriched snack products. Among freshwater fish species, Oreochromis niloticus (tilapia) is widely cultured, economical, and nutritionally superior, making it suitable for value-added product development. The present study aimed to develop protein-enriched fish-based snack chips from tilapia by optimizing composite flour formulation using RSM with a Box–Behnken Design (BBD). Fish chips were prepared using tilapia fish meat, sago flour, and potato starch as the major ingredients. Optimization of composite flour levels was carried out by selecting fish meat (20–30%), sago flour (25–35%), and potato starch (30–40%) as independent variables, while overall acceptability (OAA) and linear expansion (LE) were considered as response variables. The experimental data were statistically analyzed to determine the optimal combination of ingredients. The optimized composite flour formulation consisted of 25% fish meat, 30% sago flour, and 35% potato starch, which resulted in a high overall acceptability score of 8.31 and linear expansion of 42.92%. The results demonstrated that tilapia-based composite flour formulations could be effectively utilized to produce acceptable, protein-enriched snack chips with desirable expansion characteristics, highlighting their potential for nutritious snack development.